Island of the blue dolphins eaudiobook - O'Dell, Scott (Island of the Blue Dolphins, 2011)
"Our island is like a dolphin lying on its side, with its tail pointing toward the sunrise, its nose pointing to the sunset, and its fins making reefs and the rocky ledges along the shore." Karana, a Ghalas-at Indian, lives peacefully on the island with her tribe until the arrival of a Russian otter-hunting ship. In spite of the deal the Aleutian hunters make with her father, the Ghalas-at chief, in the end they prove treacherous, killing most of the tribe. Karana's younger brother, Ramo, is all that is left of her family. Fearful of the Aleuts' return, the remaining Indians decide to move to another island, and are offered safe passage by some friendly ships. But as Karana boards the ship to leave the island forever, she is unable to find Ramo, and swims back to shore to search for him. Abandoned by the ships, Karana must draw on reserves of resourcefulness, and courage in order to survive. Island of the Blue Dolphins is based on the true story of an Indian girl who lived for 18 years on an island off the coast of California.